Maternal and Fetal Outcome Differences in Pregnant Women with Preeclampsia and Severe Preeclampsia at Dr. Saiful Anwar General Hospital - Daniati, Lidya; Rahardjo, Bambang (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Preeclampsia is a major factor leading to complications for both mothers and infants, significantly raising maternal mortality rates in Indonesia, where severe instances result in approximately 1.5% of maternal deaths. It also heightens the chance of perinatal loss, with severe preeclampsia having a rate of around 4.6%. Frequent complications related to this condition are low birth weight, intrauterine growth restriction, asphyxia, and preterm delivery. The objective of this research was to evaluate the differences in outcomes for mothers and infants between those experiencing preeclampsia and those suffering from severe preeclampsia at Dr. Saiful Anwar General Hospital. Material and Methods: A retrospective analytical observational design was used, analyzing data from pregnant women treated at HKFM Education Center and Dr. Saiful Anwar General Hospital between January 2022 and December 2023. Statistical analysis involved the t-test or the Mann-Whitney test. Results: Findings revealed considerable variations in maternal results, such as eclampsia, elevated hypertension, and alterations in systolic blood pressure the day after delivery, among women diagnosed with preeclampsia versus those with severe preeclampsia. Distinct variations were observed in maternal well-being throughout pregnancy, during delivery, and in postpartum care. Nevertheless, fetal outcomes showed no significant disparities between the two categories, implying that the conditions for the infants during gestation and post-delivery were comparable. Conclusion: Women suffering from intense preeclampsia encountered various maternal outcomes in contrast to those without the condition, although fetal results were similar in both categories at the hospital that was examined.